Compression of daily activity time in mice lacking functional Per or Cry genes. (June 2014) - Spoelstra, K.; Comas, M.; Daan, S.
<x xml:space="preserve">Abstract</x> The adjustment of daily activity time (α) to the varying night length in nocturnal creatures was one of the functions originally attributed to a putative dual oscillator structure of circadian pacemakers in mammals. In two experimental approaches, we tested whether this ability is compromised in mice with functional deletions of one of the four circadian clock genes. First, we tested the capability of α compression by long days in mPer1Brdm1 and mPer2Brdm1 mutant mice. When exposed to a full L:D 18:6 photoperiod, wild-type and mPer1Brdm1 mutant mice show compression followed by decompression of α in DD. mPer2Brdm1 mutant mice did not compress their activity time. The interpretation of these data is, however, complicated by masking due to light. We, therefore, embarked on a second experiment, exploiting skeleton photoperiods. The skeleton photoperiod was changed stepwise from 0 to 24 h, and mCry1 and mCry2 knockout mice were now included in the design. We observed clear and systematic compression of α in wild-type and mCry1 and mCry2 knockout mice. mPer1Brdm1 and mPer2Brdm1 mice both poorly entrained to the skeleton photoperiod. The single mPer2Brdm1 mutant mouse that did entrain did not show α compression. The results show that neither mCry1 nor mCry2 deletions compromise adjustment to day length, consistent with our earlier conclusions on period lengthening in constant light (Spoelstra & Daan, 2008). The mPer2Brdm1 mutant behaves aberrantly and appears not to respond to the delaying action of light in the late subjective day.